ACTIVE POWER LOSS REDUCTION BY FIREFLY ALGORITHM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2018)
This paper proposes a swarm intelligence algorithm, called Firefly Mating Algorithm (FMA) for solving optimal reactive power problem. FMA uses genetic algorithm as the core of the algorithm. The main feature of the algorithm is a novel mating pair selection method which is inspired by the following two mating behaviours of fireflies in nature: (i) the mutual attraction between males and females causes them to mate and (ii) fireflies of both sexes are of the multiple-mating type, mating with multiple opposite sex partners. A female continues mating until her spermatheca becomes full, and, in the same vein, a male can provide sperms for several females until his sperm reservoir is depleted. In order to evaluate the efficiency of the proposed algorithm; it has been tested on IEEE 57 bus system and simulation results reveals about the best performance of the proposed algorithm in reducing the real power loss.